INSTITUTIONAL MARKETING STRATEGY OF EARLY CHILDHOOD EDUCATION PROGRAM - Sumiyati Sumiyati; Nurkhosi’in Nurkhosi’in (JCE (Journal of Childhood Education), 2019)
This research examines the imaging or marketing strategy of Early Childhood Education institutions. Research uses a qualitative approach by emphasizing the quality of data in the field. An important factor influencing the success or existence of an institution is marketing. The results of this research indicate that marketing is the spearhead of the survival of Early Childhood Education institutions. Because marketing activities carried out well will produce good profits. The findings of this study indicate that; First, marketing activities are the main activities that must be carried out by all members involved in the organization. In TK Aisyiyah 02 Pati, both teachers, employees, parents of students and even students are part of those involved in marketing activities. Both marketing activities highlight product excellence. The products intended for Early Childhood Education services, especially in TK Aisyiyah 02 Pati, are educational facilities both physical and non-physical and the quality of Human Resources developed.